Edgar A. Brown & William W. Thornton, Revision of 1904: The General Ordinances of the City of Indianapolis 551 (1904) - (:unkn) unknown (My University, 1884)
§§ 1665-1668: Prohibited operating a shooting gallery for rifles or pistols without obtaining a license. Licenses shall cost twenty-five dollars for six-months or fifty dollars for one year. Violators fined fifty dollars for each day in violation.
Keywords: SHOOTING RANGES OR GALLERIES